Generation of Chicken IgY against SARS-COV-2 Spike Protein and Epitope Mapping - Yan Lu; Yajun Wang; Zhen Zhang; Jingliang Huang; Meicun Yao; Guobin Huang; Yuanyuan Ge; Peichun Zhang; Huaxin Huang; Yong Wang; Huiliang Li; Wen Wang (Journal of Immunology Research)
This new decade has started with a global pandemic of COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), precipitating a worldwide health crisis and economic downturn. Scientists and clinicians have been racing against time to find therapies for COVID-19. Repurposing approved drugs, developing vaccines and employing passive immunization are three major therapeutic approaches to fighting COVID-19. Chicken immunoglobulin Y (IgY) has the potential to be used as neutralizing antibody against respiratory infections, and its advantages include high avidity, low risk of adverse immune responses, and easy local delivery by intranasal administration. In this study, we raised antibody against the spike (S) protein of SARS-CoV-2 in chickens and extracted IgY (called IgY-S) from egg yolk. IgY-S exhibited high immunoreactivity against SARS-CoV-2 S, and by epitope mapping, we found five linear epitopes of IgY-S in SARS-CoV-2 S, two of which are cross-reactive with SARS-CoV S. Notably, epitope SIIAYTMSL, one of the identified epitopes, partially overlaps the S1/S2 cleavage region in SARS-CoV-2 S and is located on the surface of S trimer in 3D structure, close to the S1/S2 cleavage site. Thus, antibody binding at this location could physically block the access of proteolytic enzymes to S1/S2 cleavage site and thereby impede S1/S2 proteolytic cleavage, which is crucial to subsequent virus-cell membrane fusion and viral cell entry. Therefore, the feasibility of using IgY-S or epitope SIIAYTMS-specific IgY as neutralizing antibody for preventing or treating SARS-CoV-2 infection is worth exploring.